‘Making Moves’: Protocol for a hybrid effectiveness-implementation pre-post trial of a co-designed online physical activity program for childhood cancer survivors - Lauren Ha; Claire E. Wakefield; Jacqueline Jacovou; Karen Johnston; Donna Drew; Mark W. Donoghoe; David Mizrahi; Richard De Abreu Lourenco; Richard J. Cohn; Natalie Taylor; Christina Signorelli; Kiarn Roughley; et al. (JSAMS Plus)
Background: Childhood cancer survivors are at increased risk of developing chronic health conditions, including cardiovascular disease. Cardiovascular disease risk is further exacerbated by low physical activity levels and high levels of sedentary behaviour. Yet many survivors do not meet the physical activity guidelines, and those living in regional and remote areas have limited access to exercise interventions and cancer care programs. Therefore, it is critical that physical activity programs are accessible for childhood cancer survivors, no matter where they live. This protocol describes the development and planned evaluation of ‘Making Moves’, a co-designed online physical activity program for childhood cancer survivors aged 8–21 years. Methods and analysis: This type I hybrid effectiveness-implementation pre-post trial will simultaneously (i) test the potential effectiveness of Making Moves on survivors' physical activity self-efficacy, and (ii) explore barriers and facilitators to implementation from multiple levels (individual, provider, organisational, and community) to inform future adaptations and implementation strategies. Making Moves includes an 8-week online program offering eight age-appropriate health behaviour educational modules with guided home-based physical activity videos, and up to five tailored telehealth sessions with an Accredited Exercise Physiologist. Assessment of the primary outcome (physical activity self-efficacy, i.e., perceived ability to engage in physical activity) and secondary outcomes (physical activity levels, aerobic fitness, muscular strength, symptoms of depression, readiness to exercise, perceived enjoyment of exercise, health-related quality of life) will occur at baseline (week 0), post-intervention (week 9), and follow-up (6 months). To assess the factors affecting the program’s implementation, we will conduct a process evaluation guided by the Consolidated Framework for Implementation Research 2.0 to interview survivors and parents, and future potential implementors. To judge the potential implementation success of Making Moves, we will collect implementation data (feasibility, acceptability, costs) for our process evaluation throughout the trial. Ethics and dissemination: Ethical approval was obtained from the Sydney Children’s Hospital Network Human Research Ethics Committee (2023/ETH01614). We will publish our findings in peer-reviewed journals, present findings at relevant medical and scientific conferences, and disseminate research updates via newsletters to stakeholders and community networks. Trial registration number: ANZCTR12623000188639. Registered 22 Feb 2023.